Learning styles of pharmacy students in the University of the Philippines Manila - Choi, Franchesca D.
Students learning style refers to the way respond to stimuli in a learning context, and to their characteristic way of acquiring and using information. The purpose of this study was to assess the learning style of the students at the University of the Philippines- Manila (UP Manila) College of Pharmacy and to determine their association to teaching method preferences and academic performance. A survey was conducted among 198 pharmacy students from UP Manila, using a validated, online, electronic base on the 100-item version of Vermunt's Inventory Styles (ILS). The most prevalent learning style among Pharmacy students in UP Manila across all year levels is reproduction-directed (36.4%) followed by application-directed (26.8%). In general, students favor lectures as teaching method and selected reading assignments and reporting as the preferred. Students with application-directed learning styles prefer laboratory exercises while students with meaning-directed learning styles and reproduction-directed learning styles prefer lectures. No significant relationship was found between learning style and academic performance (p=0.687). The learning style profile of the students may be built upon on, to develop meaning-directed approaches by focusing on intervention that will promote deep, critical processing and self-regulation (rather than stepwise, surface processing and external regulation).